Lactate rise detected by 1H NMR in human visual cortex during physiologic stimulation. - Prichard, J (1991)
Brain lactate concentration is usually assumed to be stable except when pathologic conditions cause a mismatch between glycolysis and respiration. Using newly developed 1H NMR spectroscopic techniques that allow measurement of lactate in vivo, we detected lactate elevations of 0.3-0.9 mM in human visual cortex during physiologic photic stimulation. The maximum rise appeared in the first few minutes; thereafter lactate concentration declined while stimulation continued. The results are consistent with a transient excess of glycolysis over respiration in the visual cortex, occurring as a normal response to stimulation in the physiologic range.